Current Trends in the Treatment of Human Epidermal Growth Factor Receptor-2 Negative Breast Cancer - Palanisamy Sivanandy,; Suresh Shanmugam ,; Rui Ying Lau ,; Jonathan Yvong Syen Chin ,; Xiao Xiang Lee ,; Yun Yun Lau ,; Wai Ching Lee ,; Iqbal Danial Said ,; Jing Ying Lee ,; Karthikayini Krishnasamy, (Journal of Pharmacy and Nutrition Sciences, 2020)
Breast cancer affect almost 1 in 8 women and it is highest in developed and developing countries. There are many drugs exist for the treatment of breast cancer, but still the incidence of mortality and morbidity are high among all cancer types in most countries. Even though the conventional therapies play a major role in the management of breast cancer, its complications are obvious and unavoidable. The newer targeted drug therapy came in place to reduce complications in some extent, but not fully. Hence, a review was aimed to analyse the efficacy and safety of newer anticancer drugs that approved for the treatment of breast cancer by US-FDA from 2017 to 2019. The Olaparib, Talazoparib, and Ribociclib are the newly approved drugs for the treatment of breast cancer during this review period. Among these new drugs, Olaparib and Talazoparib alone or in combination with other anticancer drugs considered as safe and efficacious. Patients with Olaparib or Talazoparib as monotherapy have median progression-free survival of 2.8 to 8.6 months longer and has 42-46% lower risk of death (P<0.001). A combination of conventional therapies and non-pharmacological approach are warranted for the best benefit of cancer patients and to improve their quality of life.